Paste for internal electrodes of multilayer ceramic electronic components and method for manufacturing multilayer ceramic electronic components
Patent Information
- Application Number
- JP2024157998
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2044-09-12
AI Technical Summary
【0010】 ここで開示される技術によると、積層セラミック電子部品の内部電極の形成に用いられる内部電極用ペーストが開示される。内部電極用ペーストは、銀粉末と、樹脂バインダと、有機溶剤と、二酸化チタン粉末と、を含む。銀粉末は、レーザ回折散乱法に基づく体積基準の粒度分布において、粒径の小さい側から積算値50%に相当するD50径が少なくとも1μmある。二酸化チタン粉末は、球状の二酸化チタン粒子で構成されている。かかる構成によって、積層電子部品を製造するプロセスにおける熱処理を施す工程において、銀膜の収縮開始温度をより高くすることができ、かつ、銀膜の膨張挙動を抑制することが可能となる。
Smart Images

Figure 0007640798000005 
Figure 0007640798000006 
Figure 0007640798000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a paste for internal electrodes of a multilayer ceramic electronic component and a method for producing a multilayer ceramic electronic component. [Background technology]
[0002] The paste for internal electrodes disclosed in Japanese Patent No. 2987995 consists of 0.2 to 3.0% by weight of titanium oxide particles, with the remainder consisting of conductive precious metal particles, an organic binder, and an organic solvent. The titanium oxide particles are needle-like or plate-like. The publication states that this composition can suppress the occurrence of cracks in the dielectric layer and the occurrence of peeling between the dielectric layer and the internal electrode.
[0003] The conductive paste disclosed in Japanese Patent No. 3589239 contains a conductive component and an organic vehicle component, and is used to be co-fired with a ceramic molded body obtained by laminating a plurality of green sheets. The conductive component contains conductive powder coated with a metal oxide. This conductive paste is used in via-hole connections formed in the green sheets. The publication states that when a ceramic molded body is produced using the conductive paste of this composition in a via-hole connection and then fired to obtain a ceramic multilayer substrate, the ceramic multilayer substrate can be made less susceptible to warping or deformation.
[0004] Japanese Patent No. 7489824 discloses a conductive paste for thin films used to form thin-film electrode layers with a thickness of 1 μm to 3 μm. This conductive paste contains conductive powder, manganese oxide powder, a binder, and a solvent. The manganese oxide powder has a cumulative 50% particle diameter (D 50 ) is 500 nm or less, and the cumulative 90% particle size (D 90 ) and cumulative 10% particle size (D 10 ) and the difference (D 90 -D 10) is 700 nm or less. The publication states that with this configuration, an electrode layer with excellent surface smoothness can be formed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 2987995 [Patent Document 2] Patent No. 3589239 [Patent Document 3] Patent No. 7489824 Summary of the Invention [Problem to be solved by the invention]
[0006] For example, silver powder may be used to form an internal electrode of an electronic component. The process of manufacturing an electronic component may include a step of subjecting the silver powder to a heat treatment in order to sinter the silver powder. For example, an internal electrode paste containing silver powder is used to form an internal electrode layer. In this case, the process of manufacturing an electronic component may include a step of applying an internal electrode paste to a substrate and subjecting the coating of the internal electrode paste to a heat treatment. The internal electrode paste contains organic components such as a resin binder and an organic solvent for various purposes. For example, such organic components are burned out in the step of applying the heat treatment. At this time, for example, gas derived from the organic components is generated. On the other hand, the silver powder is sintered by the step of applying the heat treatment to form a silver film. In the step of applying the heat treatment, the organic components are burned out in a relatively low temperature range, and sintering of the silver powder begins in a relatively high temperature range. As the sintering of the silver powder progresses, the silver film tends to shrink.
[0007] However, in the temperature range where the sintering of the silver powder starts, some organic components may remain. The remaining organic components burn out at the temperature range where the sintering of the silver powder starts or at a higher temperature range. At this time, if at least a part of the silver powder is sintered, gas derived from the remaining organic components is less likely to be discharged from between the silver powder. Therefore, as the sintering of the silver powder progresses, the silver film may change from a shrinking tendency to an expanding tendency. Such a change in the behavior of the silver film is undesirable because it may cause cracks to occur in the internal electrodes, for example.
[0008] In recent years, multilayer ceramic electronic components have become more diverse. Accordingly, a greater variety of substrate materials are being considered for use as substrates on which internal electrodes are provided. Depending on the substrate material, for example, the heat treatment described above may be required to be performed at a higher temperature.
[0009] In view of these circumstances, the present inventors wished to increase the temperature at which the silver film begins to shrink and also increase the temperature at which the silver film changes from a shrinking tendency to an expanding tendency in the heat treatment step in the process of manufacturing laminated electronic components. [Means for solving the problem]
[0010] According to the technology disclosed herein, there is disclosed an internal electrode paste used for forming internal electrodes of a multilayer ceramic electronic component. The internal electrode paste contains silver powder, a resin binder, an organic solvent, and titanium dioxide powder. The silver powder has a D 2 range corresponding to a cumulative value of 50% from the smallest particle size side in a volume-based particle size distribution based on a laser diffraction scattering method. 50 The titanium dioxide powder has a diameter of at least 1 μm. The titanium dioxide powder is composed of spherical titanium dioxide particles. With this composition, it is possible to increase the shrinkage start temperature of the silver film and suppress the expansion behavior of the silver film during the heat treatment step in the process of manufacturing the laminated electronic component.
[0011] According to the technology disclosed herein, a method for manufacturing a multilayer ceramic electronic component is disclosed. This manufacturing method includes applying the internal electrode paste to a substrate and firing the coating of the internal electrode paste and the substrate. With this configuration, it is possible to increase the shrinkage start temperature of the silver film and suppress the expansion behavior of the silver film in the heat treatment step in the process of manufacturing the multilayer electronic component. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view of a multilayer chip inductor 1. As shown in FIG. [Diagram 2] FIG. 2 is a graph showing the thermal analysis of Example 11. [Diagram 3] FIG. 3 is a graph of the thermal analysis of Example 17. [Figure 4] FIG. 4 is a graph of the thermal analysis of Example 21. [Diagram 5] FIG. 5 is a graph of the thermal analysis of Example 22. [Figure 6] FIG. 6 is a graph of the thermal analysis of Example 23. [Figure 7] FIG. 7 is a graph of the thermal analysis of Example 24. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, preferred embodiments of the technology disclosed herein will be described. Note that matters other than those specifically mentioned in this specification and necessary for implementing the technology disclosed herein can be understood based on the technical content taught by this specification and the general technical common sense of a person skilled in the art in the relevant field. The technology disclosed herein can be implemented based on the contents disclosed in this specification and the technical common sense of a person skilled in the art in the relevant field. Note that the description of A to B (A and B are any numerical value) in this specification and claims means A or more and B or less, and also includes the case where A is more than A and B is less than B.
[0014] According to the technology disclosed herein, an internal electrode paste for forming an internal electrode of a multilayer ceramic electronic component is disclosed. This internal electrode paste contains silver powder, a resin binder, an organic solvent, and titanium dioxide powder. The silver powder has a D 2 range corresponding to a cumulative value of 50% from the smallest particle size side in a volume-based particle size distribution based on a laser diffraction scattering method. 50 Diameter (hereinafter simply referred to as "D 50 It is a silver powder with a diameter of at least 1 μm. Titanium dioxide powder is composed of spherical titanium dioxide particles.
[0015] The inventors wanted to improve the dispersibility of the internal electrode paste in order to make the distribution of silver powder in the internal electrodes more uniform. 50 It has been found that a favorable dispersion effect can be obtained by using silver powder with a diameter of at least 1 μm. 50 It was found that when silver powder with a diameter of 10 mm was used, cracks were easily generated in the internal electrodes. 50 It was thought that the occurrence of cracks could be suppressed by increasing the shrinkage starting temperature of the silver film obtained using an internal electrode paste containing silver powder with a diameter of at least 1 μm, and the composition was investigated.
[0016] Silver powder is a component that imparts electrical conductivity to a fired film (hereinafter also referred to as "internal electrode" or "silver film") obtained by firing the internal electrode paste. Silver powder is, for example, composed of silver particles. Examples of silver particles include particles made of a single silver (Ag), particles made of an alloy containing silver (e.g., Ag / Pd alloy, Ag / Pt alloy, Ag / Cu alloy, etc.) (e.g., an alloy containing 70 mass% or more (preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more) of silver), silver-coated particles having a coating layer containing silver on the surface of a core particle, and core-shell particles in which a core particle is made of silver and a shell covering the core particle is made of a metal other than silver (e.g., palladium, platinum, copper, etc.), an alloy containing silver, etc. The silver powder may contain unavoidable impurities that are generated, for example, during the manufacturing process of silver particles. The purity of the silver powder is generally 98% or more, for example 99% or more, preferably 99.5% or more, more preferably 99.8% or more, even more preferably 99.9% or more, and the closer to 100%, the better.
[0017] Silver powder D 50 The diameter may be, for example, 1 μm or more, and may be appropriately set according to the desired function of the internal electrode. 50 The diameter is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more. On the other hand, the smaller the size of the silver particles, the higher the sintering property between the silver particles, and the lower the resistance of the internal electrode can be realized. From this viewpoint, the D 50 The diameter is, for example, 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 8 μm or less.
[0018] In the volume-based particle size distribution of silver powder based on the laser diffraction scattering method, the cumulative value of 10% from the small particle size side is D 10 Diameter (hereinafter simply referred to as "D 10 The diameter of the silver powder is set to about 0.1 μm to 10 μm in order to prevent short circuits caused by the penetration of the fine particles (silver particles) into the substrate. 10The diameter is, for example, 0.3 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 1.5 μm or more. On the other hand, from the viewpoint of improving the sinterability of the internal electrodes, D 10 The diameter is, for example, 7.5 μm or less, preferably 5 μm or less, and more preferably 3 μm or less.
[0019] In the volume-based particle size distribution of silver powder based on the laser diffraction scattering method, the D 90 Diameter (hereinafter simply referred to as "D 90 From the viewpoint of improving the heat resistance of the silver powder in the internal electrode paste, the D 90 The diameter is, for example, 5 μm or more, preferably 7 μm or more, more preferably 9 μm or more, and even more preferably 10 μm or more. From the viewpoint of making the particle size distribution sharp and improving the continuity and smoothness of the internal electrodes, the D of the silver powder is 90 The diameter is, for example, 50 μm or less, preferably 40 μm or less, more preferably 35 μm or less, and even more preferably 30 μm or less.
[0020] The shape of the silver particles constituting the silver powder is not particularly limited as long as the effects of the technology disclosed herein are achieved.
[0021] When the entire internal electrode paste is taken as 100% by mass, the content of silver powder is generally 60% by mass or more, or 70% by mass or more, for example, 80% by mass or more, preferably 85% by mass or more, and more preferably 90% by mass or more. This can improve the density of the internal electrode, for example. When the entire internal electrode paste is taken as 100% by mass, the content of silver powder is generally 99% by mass or less, for example, 98% by mass or less, preferably 97% by mass or less, and more preferably 96% by mass or less. This can add an appropriate amount of components other than silver powder to the internal electrode paste.
[0022] The resin binder is, for example, a component that binds the silver powder, the titanium dioxide powder, and the substrate when the internal electrode paste is applied (coated) onto the substrate. The resin binder is preferably a component that burns out when the internal electrode paste is fired. The type of resin binder is not particularly limited, and a resin binder that has been used in this type of conventional internal electrode paste can be used depending on, for example, the method of applying the internal electrode paste to the substrate.
[0023] Examples of the resin binder include celluloses such as methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, and polybutyl methacrylate; epoxy resins; phenolic resins; alkyd resins; polyvinyl alcohol; polyvinyl butyral; rosin, maleic rosin, and the like. As the resin binder, one of the above may be used alone, or two or more may be used in combination. When the entire internal electrode paste is taken as 100% by mass, the content of the resin binder is generally 0.1% by mass to 3% by mass, and preferably 0.3% by mass to 1% by mass.
[0024] The organic solvent is a component that dissolves or disperses, for example, silver powder, resin binder, titanium dioxide powder, and other components. The type of organic solvent is not particularly limited and can be selected from conventionally known organic solvents. For example, the organic solvent can be one type of organic solvent described below alone or two or more types in appropriate combination. Examples include alcohol-based solvents having an -OH group, ether-based solvents having an ether bond (RO-R'), ester-based solvents having an ester bond (RC(=O)-O-R'), and hydrocarbon-based solvents composed of carbon atoms and hydrogen atoms.
[0025] Examples of alcohol-based solvents and ether-based solvents include terpineol, texanol, dihydroterpineol, benzyl alcohol, 3-methoxy-3-methyl-1-butanol, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol-n-butyl ether, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, and dipropylene glycol methyl-n-butyl ether.
[0026] Examples of ester-based solvents include 3-methoxy-3-methyl-1-butanol acetate, 3-methoxybutyl acetate, 1,3-butylene glycol diacetate, 1,4-butanediol diacetate, 1,6-hexanediol diacetate, propylene glycol monomethyl ether acetate, isobornyl acetate, carbitol acetate, ethyl diglycol acetate, butyl cellosolve acetate, propylene glycol diacetate, diethylene glycol monobutyl ether acetate, terpineol acetate, dihydroterpineol acetate, etc. Examples of hydrocarbon-based solvents include aliphatic hydrocarbon solvents such as petroleum hydrocarbons, naphtha, dipentene, turpentine oil, and mineral spirits; aromatic hydrocarbon solvents such as benzene, toluene, and xylene; paraffin-based solvents such as normal paraffins and isoparaffins; naphthenic solvents such as monocyclic naphthenes and bicyclic naphthenes; and the like. When the entire internal electrode paste is taken as 100% by mass, the content of the organic solvent is generally 0.5% by mass to 10% by mass, and preferably 2% by mass to 7% by mass.
[0027] Titanium dioxide powder is, for example, a component that has a function of promoting the combustion of organic components. Therefore, by including titanium dioxide powder in the internal electrode paste, it is possible to promote the emission of gas derived from the organic components prior to the progress of sintering of the silver powder. In addition to this, titanium dioxide powder can have a function of delaying the sintering of the silver powder. Therefore, by including titanium dioxide powder in the internal electrode paste, it is possible to delay the sintering of the silver powder when the internal electrode paste is subjected to a heat treatment. The function of titanium dioxide powder will be described further below.
[0028] As described above, the titanium dioxide particles constituting the titanium dioxide powder in the internal electrode paste disclosed herein are spherical. In this specification, the term "spherical" with respect to titanium dioxide particles and other oxide particles described later means that the average aspect ratio of the titanium dioxide particles or other oxide particles is approximately 1 to 1.5, for example, 1 to 1.3, preferably 1 to 1.2, more preferably 1 to 1.15, and even more preferably 1 to 1.1. The average aspect ratio of the titanium dioxide particles or other oxide particles can be obtained, for example, by observing the titanium dioxide powder or other oxide powder (titanium dioxide particles or other oxide particles) with an SEM, randomly selecting a plurality of particles (for example, 10 to 300 particles) from the obtained observation image, calculating the aspect ratio (ratio of the major axis to the minor axis) based on the major axis and minor axis of each particle, and obtaining the arithmetic average value.
[0029] The specific surface area of the titanium dioxide powder is not particularly limited as long as the effects of the technology disclosed herein are realized. The specific surface area of the titanium dioxide powder is approximately 10 m 2 / g~150m 2 / g. The larger the specific surface area, the more effective it is in delaying the sintering of the silver powder, for example by penetrating between the silver particles in the internal electrode paste. In addition, the above-mentioned effect of promoting combustion can be enhanced. From this viewpoint, the specific surface area of the titanium dioxide powder is preferably 15 m, for example. 2 / g or more, and 2 / g or more is preferable, and 25m 2 / g or more is more preferable, and 30m 2 / g or more is more preferable. On the other hand, the smaller the specific surface area, the greater the gap between silver particles in the internal electrode paste, for example, and the greater the effect of delaying the sintering of the silver powder. In addition, it becomes easier to discharge gas derived from organic components. From this perspective, the specific surface area of the titanium dioxide powder is, for example, 150 m 2 / g or less, 140m 2 / g or less is preferable, and 130m 2 / g or less is more preferable, and 120m 2 / g or less is more preferable. The specific surface area of the titanium dioxide powder and the specific surface area of the other oxide powders described later can be calculated based on the BET method in accordance with the "Method of measuring the specific surface area of powders (solids) by gas adsorption" specified in JIS Z 8830:2013 (ISO9277:2010). Alternatively, the nominal value of the manufacturer or the like may be used.
[0030] For example, the following formula (P): DB1 = 6 / (S × ρ) (P) By using the above, it is possible to obtain the average particle diameter DB1 (nm) of the titanium dioxide powder. Here, in the above formula (P), S is the specific surface area of the titanium dioxide powder, and ρ is the density of the titanium dioxide powder. The average particle diameter DB1 of the titanium dioxide powder is not particularly limited as long as the effect of the technology disclosed herein is realized, but is generally 5 nm to 140 nm, and preferably 10 nm to 50 nm.
[0031] The internal electrode paste is, for example, 1.0×10 -3 Part of mass ~5.0×10 -2 The silver film tends to have a higher shrinkage start temperature as the titanium dioxide powder content ratio relative to 100 parts by mass of silver powder increases. From this viewpoint, the internal electrode paste preferably contains 1.5×10 -3 parts by mass or more, more preferably 2.0×10 -3parts by mass or more, more preferably 2.5×10 -3 The smaller the content ratio of titanium dioxide powder to 100 parts by mass of silver powder, the more the resistance of the internal electrode can be suppressed from increasing. From this viewpoint, the internal electrode paste preferably contains 4.5×10 -2 parts by mass or less, more preferably 4.0×10 -2 parts by mass or less, more preferably 3.5×10 -2 Contains less than parts by mass.
[0032] When the entire internal electrode paste is taken as 100 mass%, the content of titanium dioxide powder is preferably about 5 ppm to 450 ppm. From the viewpoint of increasing the shrinkage start temperature of the silver film and increasing the temperature at which the silver film changes from a shrinkage tendency to an expansion tendency, when the entire internal electrode paste is taken as 100 mass%, the content of titanium dioxide powder is, for example, 10 ppm or more, preferably 15 ppm or more, and more preferably 20 ppm or more. From the viewpoint of suppressing an increase in the resistance of the internal electrode, when the entire internal electrode paste is taken as 100 mass%, the content of titanium dioxide powder is preferably 400 ppm or less, and more preferably 350 ppm or less.
[0033] As described above, the internal electrode paste disclosed herein is 50 The paste contains silver powder having a diameter of at least 1 μm. This can improve the dispersibility of the silver powder in the internal electrode paste, and can realize an internal electrode with a more uniform distribution of silver. The internal electrode paste contains titanium dioxide powder composed of spherical titanium dioxide particles. This can increase the shrinkage start temperature of the silver film formed by applying heat to the coating film of the internal electrode paste in the process of manufacturing internal electrodes of multilayer ceramic electronic components, and can also increase the temperature at which the silver film changes from a shrinkage tendency to an expansion tendency.
[0034] The present inventors believe that the mechanism by which the above-mentioned effects are obtained is as follows, although it is not intended that the mechanism by which such effects are obtained be limited to the one described below.
[0035] Conventionally, for example, when a silver paste containing silver powder, a resin binder, and an organic solvent is subjected to heat treatment, the organic components in the silver paste burn off in a temperature range up to about 300°C. However, in order for some of the organic components to burn off, heat treatment at a higher temperature is required, and the organic components remain up to that temperature range. The remaining organic components begin to burn from the surface side in a temperature range of about 600°C, and burn off as the temperature rises. On the other hand, sintering of the silver powder begins at about 400°C. The sintering of the silver powder progresses as the temperature rises, and a silver film is formed. As the sintering of the silver powder progresses, the silver film shrinks, but, for example, the emission of gas derived from the remaining organic components is hindered. For this reason, the silver film may begin to expand.
[0036] The titanium dioxide powder contained in the internal electrode paste has, for example, a catalytic action to promote the combustion of organic components. Therefore, the titanium dioxide powder can promote the combustion of the remaining organic components before the sintering of the silver powder proceeds. In other words, if the internal electrode paste contains titanium dioxide powder, when the coating of the paste is subjected to a heat treatment, the applied heat can be used to burn the remaining organic components before it is used to sinter the silver powder. Therefore, it is possible to suppress the residue of organic matter in the silver film. Furthermore, the titanium dioxide powder can enter between the silver particles constituting the silver powder and delay the progress of the sintering of the silver powder. By using the titanium dioxide powder in a spherical shape, the silver powder and the titanium dioxide powder in the coating of the internal electrode paste can be more uniformly dispersed, and the filling properties of both powders can be improved. Therefore, the effect of delaying the progress of the sintering of the silver powder can be enhanced, and the gas generated during the heat treatment process can be easily discharged. This makes it possible to suppress the silver film from changing from contraction to expansion, or to raise the temperature at which the silver film changes from contraction to expansion, thereby making it possible to carry out the heat treatment at a higher temperature.
[0037] Although not particularly limited, the internal electrode paste disclosed herein may further contain other oxide powders different from titanium dioxide powder (hereinafter, simply referred to as "other oxide powders") as necessary. The other oxide powders can, for example, enter between the silver particles constituting the silver powder and delay the progress of sintering of the silver powder. By containing both titanium dioxide powder and other oxide powder in the internal electrode paste, the effect of delaying the progress of sintering of the silver powder can be further enhanced than when titanium dioxide powder is contained alone. For this reason, for example, it is possible to better realize the discharge of gas generated by the catalytic action of titanium dioxide powder, and the effect of suppressing the contraction of the silver film from turning into expansion, or the effect of increasing the temperature at which the contraction of the silver film turns into expansion, can be further enhanced. This makes it possible to carry out the above heat treatment at a higher temperature than when titanium dioxide powder is contained alone.
[0038] The other oxide powder is not particularly limited as long as the effect of the technology disclosed herein is realized, and an oxide powder used for this type of application is used. The other oxide powder preferably contains at least one of alumina, silica, zirconia, ceria, yttria, zeolite, copper oxide, iron oxide, zinc oxide, etc. Among them, from the viewpoint of further enhancing the effect of suppressing the silver film from shrinking to expanding, or the effect of further increasing the temperature at which the silver film shrinks to expanding, it is preferable that the other oxide powder contains silica and / or alumina.
[0039] The shape of the other oxide particles constituting the other oxide powder is not particularly limited as long as the effect of the technology disclosed herein is realized. The shape of the other oxide particles may be either spherical or non-spherical, but is preferably spherical.
[0040] The specific surface area of the other oxide powder is not particularly limited as long as the effect of the technology disclosed herein is realized. The specific surface area of the other oxide powder is approximately 50 m 2 / g~150m2 The larger the specific surface area of the other oxide powder, the greater the effect of retarding the sintering of the silver powder, for example by penetrating between silver particles in the internal electrode paste. From this viewpoint, the specific surface area of the other oxide powder is preferably, for example, 55 m 2 / g or more, 60m 2 / g or more is preferable, and 65m 2 / g or more is more preferable, and 70m 2 / g or more is more preferable. On the other hand, the smaller the specific surface area of the other oxide powder, the greater the effect of delaying the sintering of the silver powder, for example, by widening the gaps between the silver particles in the internal electrode paste. This makes it easier to discharge gas derived from the organic components. From this perspective, the specific surface area of the other oxide powder is, for example, 140 m 2 / g or less, 130m 2 / g or less is preferable, and 120m 2 / g or less is more preferable.
[0041] For example, the following formula (Q): DB2 = 6 / (S × ρ) (Q) By using the above, the average particle diameter DB2 (nm) of the other oxide powder can be obtained. Here, in the above formula (Q), S is the specific surface area of the other oxide powder, and ρ is the density of the other oxide powder. The average particle diameter DB2 of the other oxide powder is not particularly limited as long as the effect of the technology disclosed herein is realized, but is generally 5 nm to 50 nm, and preferably 10 nm to 40 nm.
[0042] From the viewpoint of realizing the effects of the technology disclosed herein, the mass ratio of the titanium dioxide powder to the other oxide powder (titanium dioxide powder: other oxide powder) is, for example, 1:9 to 9:1, and preferably 1:4 to 4:1. Although not particularly limited, by relatively increasing the mass ratio of the other oxide powder among the titanium dioxide powder and the other oxide powder, the effect of delaying the progress of sintering of the silver powder can be enhanced. Therefore, for example, the gas generated by the catalytic action of the titanium dioxide powder can be more effectively discharged, so that the contraction start temperature of the silver film can be increased and the expansion of the silver film can be easily suppressed.
[0043] When the internal electrode paste contains both titanium dioxide powder and other oxide powder, the total content ratio of the titanium dioxide powder and other oxide powder to 100 parts by mass of silver powder in the internal electrode paste is, for example, 1.0 × 10 -3 Part of mass ~5.0×10 -2 The greater the combined content ratio of titanium dioxide powder and other oxide powder relative to 100 parts by mass of silver powder, the higher the shrinkage start temperature of the silver film tends to be. From this viewpoint, the internal electrode paste preferably contains 1.5×10 titanium dioxide powder and other oxide powder in total relative to 100 parts by mass of silver powder. -3 parts by mass or more, more preferably 2.0×10 -3 parts by mass or more, more preferably 2.5×10 -3 The smaller the combined content ratio of titanium dioxide powder and other oxide powders per 100 parts by mass of silver powder, the more the resistance of the internal electrode can be suppressed from increasing. From this viewpoint, the combined content ratio of titanium dioxide powder and other oxide powders per 100 parts by mass of silver powder is preferably 4.5×10 -2 parts by mass or less, more preferably 4.0×10 -2 parts by mass or less, more preferably 3.5×10 -2 Contains less than parts by mass.
[0044] Although not particularly limited, from the viewpoint of realizing the effects of the technology disclosed herein, in a preferred embodiment, the internal electrode paste is 1.0×10 -3 Part of mass ~1.0×10 -2 parts by mass of titanium dioxide powder and 1.0×10 -3 Part of mass ~1.0×10 -2 In a more preferred embodiment from the viewpoint of achieving the effects of the technology disclosed herein, the internal electrode paste contains 2.0×10 -3 Part of mass ~8.0×10 -3 parts by mass of titanium dioxide powder and 2.0×10 -3 Part of mass ~8.0×10 -3 parts by weight of an oxide powder.
[0045] The internal electrode paste may contain various additive components in addition to the above-mentioned components. As the additive components, conventionally known additive components used for this type of application may be used. Examples of the additive components include inorganic fillers (excluding the above-mentioned titanium dioxide powder and the above-mentioned other oxide powders), dispersants, surfactants, viscosity adjusters, defoamers, plasticizers, antioxidants, pigments, etc. When the entire internal electrode paste is taken as 100% by mass, the content of the additive components is generally 5% by mass or less, for example 3% by mass or less, preferably 2% by mass or less, and more preferably 1% by mass or less.
[0046] According to the technology disclosed herein, a method for manufacturing a multilayer ceramic electronic component is provided. The method includes applying the internal electrode paste to a substrate, and firing the coating of the internal electrode paste and the substrate. In this embodiment, the method includes a preparing step, an applying step, and a firing step.
[0047] The preparation step is, for example, a step of preparing silver powder, titanium dioxide powder, and, if necessary, other oxide powders. In this embodiment, in the preparation step, an internal electrode paste is prepared. The internal electrode paste is prepared, for example, by mixing the above-mentioned components. As a mixer for mixing, a conventionally known mixer used for this type of application can be used without any particular limitation.
[0048] The coating step is, for example, a step of coating the internal electrode paste on the substrate. As a means for coating the internal electrode paste, a conventionally known method used for this type of application may be adopted, and for example, various printing methods such as screen printing, gravure printing, offset printing, and inkjet printing; a doctor blade method; a spray method; and the like are preferably used.
[0049] The firing step is, for example, a step of subjecting the substrate and the coating film of the internal electrode paste applied on the substrate after the coating step to a heat treatment (firing treatment). In this embodiment, in the firing step, the substrate and the coating film of the internal electrode paste applied on the substrate after the coating step are heat treated. The conditions of the heat treatment (firing treatment) are not particularly limited and can be appropriately set depending on the application of the electronic component, the material of the substrate, and the like. The temperature of the heat treatment may be set, for example, to a temperature at which the organic components in the internal electrode paste are burned out and the silver powder is sintered. The temperature of the heat treatment may be set, for example, to 500°C to 1000°C (for example, 600°C to 900°C, or 600°C to 800°C). The time of the heat treatment may be set, for example, to 30 minutes to 10 hours. The atmosphere during the heat treatment may be, for example, an air atmosphere, or an inert atmosphere such as a nitrogen atmosphere or a rare gas atmosphere.
[0050] The manufacturing method of the multilayer ceramic electronic component disclosed herein is not limited to the above-mentioned embodiment. For example, this manufacturing method may include any other steps in addition to the above-mentioned steps. This manufacturing method may include, for example, a drying step, a pressing step, etc., as necessary. The drying step is, for example, a step of volatilizing the organic solvent in the internal electrode paste, and may be performed between the application step and the firing step. The drying conditions are not particularly limited, and may be appropriately set depending on the type and amount of the organic solvent used. The pressing step is, for example, a step of pressing the silver powder applied to the base material, and may be performed between the application step and the firing step. The pressing conditions are not particularly limited, and may be appropriately set depending on the application of the multilayer ceramic electronic component, the desired thickness of the internal electrode (layer), etc.
[0051] A multilayer chip inductor, which is an example of an electronic component, will be described below. Fig. 1 is a schematic cross-sectional view of a multilayer chip inductor 1. Note that the dimensional relationships (length, width, thickness, etc.) in Fig. 1 do not necessarily reflect the actual dimensional relationships. The symbols X and Z in the drawing represent the left-right and up-down directions, respectively. However, these are merely directions for the convenience of explanation.
[0052] 1 is not particularly limited, but may be, for example, a 1608 shape (1.6 mm×0.8 mm), a 2520 shape (2.5 mm×2.0 mm), etc. The multilayer chip inductor 1 includes a main body 10 and an external electrode 20.
[0053] The multilayer chip inductor 1 includes a main body 10 and external electrodes 20 provided on both side surfaces of the main body 10 in the left-right direction X. In the main body 10, for example, a plurality of magnetic layers 12 are laminated in the up-down direction Z and integrated with each other. Examples of materials constituting the magnetic layers 12 include metal materials such as ferrite magnetic materials such as Ni-Cu-Zn ferrite, Fe-Cr-Si alloys, Fe-Al-Si alloys, and Fe-Si-M soft magnetic alloys (wherein M is at least one of chromium, aluminum, and titanium).
[0054] Between each of the magnetic layers 12, a coil conductor is provided as an internal electrode layer 14. In this embodiment, the coil conductor is a fired film of the internal electrode paste disclosed herein. Two coil conductors adjacent to each other in the vertical direction Z sandwiching the magnetic layer 12 are electrically connected through a via hole provided in the magnetic layer 12. As a result, the internal electrode layer 14 is configured in a three-dimensional coil shape (spiral shape). Both ends of the coil conductor are connected to the external electrodes 20, respectively.
[0055] The laminated chip inductor 1 can be manufactured, for example, by the following procedure. First, a magnetic paste containing a metal material constituting the magnetic layer 12, a binder, and an organic solvent is prepared, and this is supplied onto a carrier sheet to form a green sheet. Next, the green sheet is rolled and dried. The green sheet is then cut to a desired size to obtain a plurality of magnetic layer forming sheets. Next, via holes are formed at predetermined positions of the magnetic layer forming sheets using a punch or the like. Next, the internal electrode paste disclosed herein is printed in a predetermined coil pattern at predetermined positions of the plurality of magnetic layer forming sheets, and dried. Next, these are stacked and pressed to produce a laminate of unfired green sheets. By firing this, the green sheets are fired integrally, and a main body 10 having a magnetic layer 12 and an internal electrode layer 14 is formed. Then, an appropriate external electrode forming paste is applied to both ends of the main body 10, and fired to form an external electrode 20. In this manner, the laminated chip inductor 1 can be manufactured.
[0056] Test examples relating to the technology disclosed herein will be described below, but it is not intended that the technology disclosed herein be limited to the following test examples.
[0057] <Test 1> --Example 11-- Silver powder A was prepared. The particle size distribution of silver powder A was analyzed, and D 10 The diameter is 2.0 μm, D 50 The diameter is 5.3 μm, D 90The diameter was 12 μm. Microtrac's "MT3300EX" was used to analyze the particle size distribution of the silver powder. Ethyl cellulose was prepared as the resin binder. Diethylene glycol monobutyl ether acetate was prepared as the organic solvent. Titanium dioxide powder A was prepared as the additive. Titanium dioxide powder A was spherical and had a specific surface area of 70 m 2 / g~110m 2 / g and density is 4.3g / cm 3 The particle diameter was calculated using the above formula (P).
[0058] The prepared silver powder A, resin binder, organic solvent, and titanium dioxide powder A were mixed using a mixer to prepare a silver paste. Here, when the entire silver paste is taken as 100 mass%, the content of silver powder A was 95 mass%, the content of resin binder was 0.68 mass%, the content of titanium dioxide powder A was 0.01 mass% (100 ppm), and the content of the remaining organic solvent was 4.31 mass%. In the silver paste, 1.1×10 -2 The silver paste contained titanium dioxide powder A in an amount of 100 parts by mass. The silver paste was then dried and pulverized to obtain a paste powder. The paste powder was then filled into a mold using a uniaxial molding machine (Towa Seiki Co., Ltd. hydraulic press PHK5-S) and pressed in the axial direction at a pressure of 78 MPa to obtain a cylindrical pellet of the paste powder having a diameter of 8 mm.
[0059] Then, the pellets were subjected to thermal analysis (TMA) using a thermomechanical analyzer (thermal analyzer TMA8310 manufactured by Rigaku Corporation). In the thermal analysis, the pellets were heated from room temperature to 800°C at a heating rate of 5°C / min in an air atmosphere. The length of the pellet at 350°C (hereinafter also referred to as "reference length") was the change in length from 350°C to 800°C, which was the shrinkage rate (%). In the thermal analysis, the temperature at which the shrinkage rate was 1% was obtained at the temperature at which the pellets tended to shrink. The results are shown in "1% shrinkage temperature (°C)" in Table 1. Furthermore, the shrinkage rate (%) at 800°C was obtained. The results are shown in "800°C shrinkage rate (%)" in Table 1. Furthermore, it was confirmed that the pellets, which tended to shrink, did not change to an expansion rate by 800°C. The results are shown in the "Expansion" column in Table 1. FIG. 2 shows a graph of the thermal analysis of this example. FIG. 2 shows a graph of the thermal analysis of Example 11. In FIG. 2, the X-axis is temperature and the Y-axis is shrinkage rate.
[0060] --Example 12-- Titanium dioxide powder B was used in place of titanium dioxide powder A. Except for this, the pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which they showed a shrinkage rate of 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which tended to shrink, did not change to a tendency to expand up to 800°C. The results are shown in the corresponding columns in Table 1. Titanium dioxide powder B was spherical and had a specific surface area of 35 m2. 2 / g~65m 2 / g and density is 4.3g / cm 3 The particle size was 22 nm to 40 nm.
[0061] --Example 13-- Silica powder A was used instead of titanium dioxide powder A. Except for that, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which the shrinkage rate was 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which tended to shrink, started to expand by 800°C. The results are shown in the corresponding columns in Table 1. Silica powder A was spherical and had a specific surface area of 50 m2. 2 / g~70m 2 / g and density is 2.7g / cm 3 The particle size was 32 nm to 45 nm.
[0062] --Example 14-- Alumina powder was used instead of titanium dioxide powder A. Except for this, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which the shrinkage rate was 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which tended to shrink, started to expand by 800°C. The results are shown in the corresponding columns in Table 1. The alumina powder was spherical and had a specific surface area of 85 m2. 2 / g~115m 2 / g and density is 4.0g / cm 3 The particle size was 13 nm to 18 nm.
[0063] --Example 15-- Copper oxide powder was used instead of titanium dioxide powder A. Except for this, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which the shrinkage rate was 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which tended to shrink, started to expand by 800°C. The results are shown in the corresponding columns in Table 1. The copper oxide powder was polyhedral and had a specific surface area of 10 m 2 / g~30m 2 / g and density is 6.3g / cm 3 The particle size was 32 nm to 95 nm.
[0064] --Example 16-- Instead of titanium dioxide powder A, a milky white zirconia colloidal aqueous solution was used. Except for that, the pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which they showed a shrinkage rate of 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which tended to shrink, turned to a tendency to expand by 800°C. The results are shown in the corresponding columns in Table 1. The D of the zirconia particles in the milky white zirconia colloidal aqueous solution was calculated using the same materials and procedures as in Example 11, and the shrinkage rate at 800°C was calculated. 50 The diameter was 60 nm to 105 nm.
[0065] --Example 17-- Pellets of this example were produced using the same materials and procedures as in Example 11, except that titanium dioxide powder A was not used, and the temperature at which the shrinkage rate was 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which tended to shrink, started to expand by 800°C. The results are shown in the corresponding columns in Table 1. Figure 3 is a graph of the thermal analysis of Example 17. In Figure 3, the X-axis is temperature and the Y-axis is shrinkage rate.
[0066] A negative shrinkage rate (%) indicates that the pellet heated to 800°C has shrunk relative to the reference length. A positive shrinkage rate (%) indicates that the pellet heated to 800°C has expanded relative to the reference length. When the 1% shrinkage temperature (°C) is in the range of 350°C to 800°C and the shrinkage rate (%) is a positive value, it indicates that the pellet first shrinks due to the heating, but then expands in the range of 350°C to 800°C (see FIG. 3). The same explanation applies to Tables 1 to 4.
[0067] [Table 1]
[0068] As shown in Table 1, comparing Examples 11 and 12 with Examples 13 to 17, in Examples 11 and 12, the 1% shrinkage temperature of the pellets was higher and the pellets were in a shrinkage state at 800°C. Furthermore, in the thermal analysis up to 800°C, the pellets in Examples 11 and 12 did not change from a shrinkage tendency to an expansion tendency, whereas the pellets in Examples 13 to 17 changed from a shrinkage tendency to an expansion tendency. As described above, the silver pastes prepared in Examples 11 and 12 contained silver powder, a resin binder, an organic solvent, and titanium dioxide powder. The silver powder was D 50 The titanium dioxide powder consisted of spherical titanium dioxide particles having a diameter of at least 1 μm.
[0069] --Example 111-- The content of titanium dioxide powder A in the silver paste is 2.5 x 10 -3 The content of the organic solvent was adjusted to 2.6 × 10 mass% (25 ppm) for 100 mass parts of silver powder A in the silver paste. -3 parts by mass of titanium dioxide powder A was included. Except for that, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which they showed a shrinkage rate of 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which had a tendency to shrink, did not change to a tendency to expand up to 800°C. The results are shown in the corresponding columns in Table 2.
[0070] --Example 112-- The content of titanium dioxide powder A in the silver paste is 5.0 x 10 -3 The content of the organic solvent was adjusted to 5.3 × 10 mass% (50 ppm) for 100 mass parts of silver powder A in the silver paste. -3 parts by mass of titanium dioxide powder A was included. Except for that, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which they showed a shrinkage rate of 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which had a tendency to shrink, did not change to a tendency to expand up to 800°C. The results are shown in the corresponding columns in Table 2.
[0071] --Example 113-- The content of titanium dioxide powder A in the silver paste is 7.5 x 10 -3 The content of the organic solvent was adjusted to 7.9 × 10 mass% (75 ppm) for 100 mass parts of silver powder A in the silver paste. -3 parts by mass of titanium dioxide powder A was included. Except for that, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which they showed a shrinkage rate of 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which had a tendency to shrink, did not change to a tendency to expand up to 800°C. The results are shown in the corresponding columns in Table 2.
[0072] --Example 114-- The content of titanium dioxide powder A in the silver paste is 1.5 x 10 -2The content of the organic solvent was adjusted to 1.6 × 10 mass% (150 ppm) for 100 mass parts of silver powder A in the silver paste. -2 parts by mass of titanium dioxide powder A. Except for that, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which the shrinkage rate of 1% was shown and the shrinkage rate at 800°C were calculated. The results are shown in the corresponding columns of Table 2.
[0073] --Example 115-- The content of titanium dioxide powder A in the silver paste was set to 0.03 mass% (300 ppm), and the content of the organic solvent was adjusted to 3.2 × 10 per 100 mass parts of silver powder A in the silver paste. -2 parts by mass of titanium dioxide powder A was included. Except for that, pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which they showed a shrinkage rate of 1% and the shrinkage rate at 800°C were calculated. It was confirmed that the pellets, which had a tendency to shrink, did not change to a tendency to expand up to 800°C. The results are shown in the corresponding columns in Table 2.
[0074] [Table 2]
[0075] In Table 2, the results of Example 11 and Example 17 are shown together for reference. As shown in Table 2, when Example 11 and Examples 111 to 115 are compared with Example 17, it was found that in Example 11 and Examples 111 to 115, which contain titanium dioxide powder (here, titanium dioxide powder A) in the silver paste, the 1% shrinkage temperature of the pellet is higher than that of Example 17, which does not contain titanium dioxide powder, and the pellet is in a shrink state at 800°C. Furthermore, looking at the results of Example 11 and Examples 111 to 115, it was found that the 1% shrinkage temperature of the pellet is higher depending on the content ratio of titanium dioxide powder. Furthermore, in the thermal analysis up to 800°C, the pellet did not change from a shrinking tendency to an expanding tendency in Example 11 and Examples 111 to 115.
[0076] <Test 2> --Example 21-- Silver powder B was prepared. The particle size distribution of silver powder B was analyzed and found to be D 10 The diameter is 2.6 μm, D 50 The diameter is 6.7 μm, and D 90 The diameter was 27 μm. Microtrac's "MT3300EX" was used to analyze the particle size distribution of the silver powder. The temperature in the thermal analysis was raised to 900 ° C. Other than that, the pellets of this example were produced using the same materials and procedures as in Example 11, and the temperature at which the shrinkage rate of 1% and the shrinkage rate at 800 ° C. were calculated. The results are shown in the corresponding columns of Table 3. In addition, the temperature at which the pellets change from a shrinkage tendency to an expansion tendency was obtained. The results are shown in "Reversal temperature (° C.)" in Table 3. Figure 4 is a graph of the thermal analysis of Example 21. In Figure 4, the X-axis is temperature and the Y-axis is shrinkage rate.
[0077] --Example 22-- The silver paste contained titanium dioxide powder A and silica powder B. Silica powder B was spherical and had a specific surface area of 75 m 2 / g~105m 2 / g and density is 2.7g / cm 3 The particle size was 22 nm to 30 nm. The content of titanium dioxide powder A in the silver paste was 5.0 × 10 -3 The content of silica powder B in the silver paste is 5.0×10 -3 The content of the organic solvent was adjusted to 5.3 × 10 mass% (50 ppm) for 100 mass parts of silver powder B in the silver paste. -3 Part by mass of titanium dioxide powder A and 5.3 x 10 -3 parts by mass of silica powder B. Except for that, pellets of this example were produced using the same materials and procedures as in Example 21, and the temperature at which the shrinkage rate of 1%, the shrinkage rate at 800°C, and the inversion temperature were calculated. The results are shown in the corresponding columns of Table 3. Figure 5 is a graph of the thermal analysis of Example 22. In Figure 5, the X-axis is temperature and the Y-axis is shrinkage rate.
[0078] --Example 23-- Titanium dioxide powder A and the above-mentioned alumina powder were added to the silver paste. The content of titanium dioxide powder A in the silver paste was 5.0×10 -3 The content of alumina powder in the silver paste is 5.0×10 -3 The content of the organic solvent was adjusted to 5.3 × 10 mass% (50 ppm) for 100 mass parts of silver powder A in the silver paste. -3 Part by mass of titanium dioxide powder A and 5.3 x 10 -3 parts by mass of alumina powder. Except for that, the pellets of this example were produced using the same materials and procedures as in Example 21, and the temperature at which the shrinkage rate of 1%, the shrinkage rate at 800°C, and the reversal temperature were calculated. The results are shown in the corresponding columns of Table 3. Figure 6 is a graph of the thermal analysis of Example 23. In Figure 6, the X-axis is temperature and the Y-axis is shrinkage rate.
[0079] --Example 24-- Pellets of this example were produced using the same materials and procedures as in Example 21, except that titanium dioxide powder A was not included in the silver paste, and the temperature at which the shrinkage rate of 1% was shown, the shrinkage rate at 800°C, and the inversion temperature were calculated. The results are shown in the corresponding columns in Table 3. Figure 7 is a graph of the thermal analysis of Example 24. In Figure 7, the X-axis is temperature and the Y-axis is shrinkage rate.
[0080] [Table 3]
[0081] As shown in Table 3, comparing Example 21 and Example 24, it was found that in Examples 21 to 23, which contain titanium dioxide powder (here, titanium dioxide powder A) in the silver paste, the 1% shrinkage temperature of the pellets is higher than in Example 24, which does not contain titanium dioxide powder, and the pellets enter a shrink state at 800°C and have a higher reversal temperature (°C). Furthermore, looking at the results of Examples 22 and 23, the pellets did not change from a shrinking tendency to an expanding tendency in the temperature range up to 900°C.
[0082] --Example 221-- The silver paste contained titanium dioxide powder A and silica powder B. The content of titanium dioxide powder A in the silver paste was 2.5×10 -3 The content of silica powder B in the silver paste is 7.5×10 -3 The content of the organic solvent was adjusted to 2.6 × 10 mass% (75 ppm) for 100 mass parts of silver powder A in the silver paste. -3 Part by mass of titanium dioxide powder A and 7.9 x 10 -3 parts by mass of silica powder B. Except for this, pellets of this example were produced using the same materials and procedures as in Example 21, and the temperature at which the shrinkage rate of 1% was shown, the shrinkage rate at 800°C, and the inversion temperature were calculated. The results are shown in the corresponding columns of Table 4.
[0083] --Example 222-- The silver paste contained titanium dioxide powder A and silica powder B. The content of titanium dioxide powder A in the silver paste was 7.5×10 -3 The content of silica powder B in the silver paste is 2.5×10 -3 The content of the organic solvent was adjusted to 7.9 × 10 mass% (25 ppm) for 100 mass parts of silver powder A in the silver paste. -3 Part by mass of titanium dioxide powder A and 2.6 x 10 -3 parts by mass of silica powder B. Except for this, pellets of this example were produced using the same materials and procedures as in Example 21, and the temperature at which the shrinkage rate of 1% was shown, the shrinkage rate at 800°C, and the inversion temperature were calculated. The results are shown in the corresponding columns of Table 4.
[0084] --Example 223-- Silica powder B was added to the silver paste. The content of silica powder B in the silver paste was set to 0.01 mass% (100 ppm), and the content of the organic solvent was adjusted. In the silver paste, the content of silica powder B was 1.1 × 10 -2Parts by mass of silica powder B were included. Except for this, pellets of this example were produced using the same materials and procedures as in Example 21, and the temperature at which the shrinkage rate of 1% was shown, the shrinkage rate at 800°C, and the inversion temperature were calculated. The results are shown in the corresponding columns of Table 4.
[0085] [Table 4]
[0086] For reference, the results of Example 21, Example 22, and Example 24 are shown in Table 4. As shown in Table 4, in Example 221, Example 22, and Example 222, which contain titanium dioxide powder and silica powder in the silver paste, the pellets did not change from a shrinking tendency to an expanding tendency in the temperature range up to 900°C.
[0087] The technology disclosed herein may include the following items. Section 1: An internal electrode paste used to form an internal electrode of a multilayer ceramic electronic component, comprising: In the volume-based particle size distribution based on the laser diffraction scattering method, D corresponds to the cumulative value of 50% from the smallest particle size side. 50 Silver powder having a diameter of at least 1 μm; A resin binder; An organic solvent; A titanium dioxide powder composed of spherical titanium dioxide particles; A paste for an internal electrode comprising: Section 2: D in the particle size distribution of the silver powder 10 Item 2. The internal electrode paste according to item 1, wherein the diameter is 1 μm or more and 3 μm or less. Section 3: D in the particle size distribution of the silver powder 90 Item 3. The internal electrode paste according to item 1 or 2, wherein the diameter is 10 μm or more and 15 μm or less. Section 4: 1.0×10 for 100 parts by mass of the silver powder -3 Mass part or more 5.0×10 -2Item 4. The internal electrode paste according to any one of items 1 to 3, comprising the titanium dioxide powder in an amount of 0.01 parts by mass or less. Section 5: 5. The internal electrode paste according to any one of items 1 to 4, further comprising another oxide powder different from the titanium dioxide powder. Item 6: Item 6. The internal electrode paste according to item 5, wherein the other oxide powder contains at least one of alumina and silica. Section 7: Item 7. The internal electrode paste according to item 5 or 6, wherein a mass ratio of the titanium dioxide powder to the other oxide powder (titanium dioxide powder: other oxide powder) is 1:9 or more and 9:1 or less. Section 8: For 100 parts by mass of the silver powder, 1.0×10 -3 Mass part or more 1.0×10 -2 parts by weight or less of the titanium dioxide powder; 1.0×10 -3 Mass part or more 1.0×10 -2 parts by weight or less of the other oxide powder; Item 8. The internal electrode paste according to any one of items 5 to 7, comprising: Section 9: Item 9. A method for producing a multilayer ceramic electronic component, comprising: applying the internal electrode paste according to any one of items 1 to 8 to a substrate; and firing the coating of the internal electrode paste and the substrate. [Explanation of symbols]
[0088] 1 Multilayer chip inductor 10 Main unit 12 Magnetic layer 14 Internal electrode layer 20 External electrode
Claims
1. An internal electrode paste used to form an internal electrode of a multilayer ceramic electronic component, comprising: In the volume-based particle size distribution based on the laser diffraction scattering method, the D 50 Silver powder having a diameter of at least 1 μm; A resin binder; An organic solvent; A titanium dioxide powder composed of spherical titanium dioxide particles; Including, The internal electrode paste, wherein the silver powder has a D 10 diameter in the particle size distribution of 1 μm or more and 3 μm or less.
2. D in the particle size distribution of the silver powder 90 The internal electrode paste according to claim 1 , wherein the diameter is 10 μm or more and 15 μm or less.
3. An internal electrode paste used to form an internal electrode of a multilayer ceramic electronic component, comprising: A silver powder having a D 50 diameter of at least 1 μm, which corresponds to an integrated value of 50% from the small particle size side in a volume-based particle size distribution based on a laser diffraction scattering method; A resin binder; An organic solvent; A titanium dioxide powder composed of spherical titanium dioxide particles; Including, 1.0 × 10 for 100 parts by mass of the silver powder -3 Mass parts or more 5.0 x 10 -2 parts by weight of said titanium dioxide powder.
4. An internal electrode paste used to form an internal electrode of a multilayer ceramic electronic component, comprising: A silver powder having a D 50 diameter of at least 1 μm, which corresponds to an integrated value of 50% from the small particle size side in a volume-based particle size distribution based on a laser diffraction scattering method; A resin binder; An organic solvent; A titanium dioxide powder composed of spherical titanium dioxide particles; Another oxide powder different from the titanium dioxide powder; Including, The mass ratio of the titanium dioxide powder to the other oxide powder (titanium dioxide powder:other oxide powder) is 1:9 or more and 9:1 or less.
5. An internal electrode paste used to form an internal electrode of a multilayer ceramic electronic component, comprising: A silver powder having a D 50 diameter of at least 1 μm, which corresponds to an integrated value of 50% from the small particle size side in a volume-based particle size distribution based on a laser diffraction scattering method; A resin binder; An organic solvent; A titanium dioxide powder composed of spherical titanium dioxide particles; Another oxide powder different from the titanium dioxide powder; Including, Relative to 100 parts by mass of the silver powder, 1.0 x 10 -3 Mass part or more 1.0×10 -2 parts by weight or less of the titanium dioxide powder; 1.0 x 10 -3 Mass part or more 1.0×10 -2 parts by weight or less of the other oxide powder; A paste for an internal electrode comprising:
6. The internal electrode paste described in claim 4 or 5, wherein the other oxide powder contains at least one of alumina and silica.
7. A method for producing a multilayer ceramic electronic component, comprising: applying the internal electrode paste according to any one of claims 1 to 5 to a substrate; and firing the coating of the internal electrode paste and the substrate.
8. A method for manufacturing a multilayer ceramic electronic component, comprising applying the internal electrode paste described in claim 6 to a substrate, and firing the coating of the internal electrode paste and the substrate.
Citation Information
Patent Citations
Photosensitive conductive paste and manufacturing method of electronic component using the same
JP2017182901A
Conductive composition, metallized substrate and method for producing the same
JP2020177908A
Internal electrode paste and multilayer ceramic capacitor using the same
JP2987995B2
Conductive pastes and ceramic compacts
JP3589239B2
Conductive paste for thin films and its use
JP7489824B2